Performance enhancement of built-up cold-formed steel beams with diagonal rebars in web. (2021) - Samuel, J.; Pravin, J.; Divahar, R.; Aravind Raj, P.S.; Joanna, P.S.
Abstract: Built-up beams that have thin webs are susceptible to buckling. In plate girders stiffeners are usually provided to enhance the overall post-buckling strength. Provision of congruent diagonal rebars is a novel concept to enhance the load carrying capacity under loading. I-section is ubiquitously used in the construction industry around the world. The results of an experimental study performed on six built-up I-section cold-formed steel (CFS) beams that are 200 mm deep are presented in this paper. All the specimens were subject to symmetric four-point bending. The nature of loading and this beam's configuration theoretically compartmentalizes the beam into three panels with a central panel subjected to constant flexure and two outer panels in constant shear. Tests were performed on the beams with and without diagonal rebars in the central panel and outer panels. The investigation results from physical phenomena like load–deflection and load–strain curves are studied for three variants of beam specimens. The investigation establishes that Cold-Formed steel beam with reinforcing bars in shear and flexure panels has the maximum load carrying capacity amongst the three types of beam specimens.